Analysis of microbiota profile and nutritional status in male professional football players - Kenger, E. B.; Eren, F.; Ozlu, T.; Gunes, F. E. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The interest in the effect of gut microbiota on athlete health has increased in recent years. Available data indicate a relationship between gut microbiota composition and physical activity, suggesting that changes in the microbiota may contribute to the host`s physical performance. Studies show that leaky gut syndrome is highly correlated with upper respiratory infections and gastrointestinal disorders in endurance sports. This study aims to reveal the relationship between microbiota profiles, and the nutritional status of football players who perform endurance exercises. METHODS: Twenty male professional football players playing in one of the Turkish Football Federation Second League clubs participated in the study. Fecal samples were collected and stored at -86 °C, and the fecal microbiota was analyzed through 16s rRNA gene sequencing. The body composition of the football players was measured using a bioelectrical impedance analyzer. In addition, the 3-day food intake of the participants was recorded with the help of a dietitian. RESULTS: In the microbiota of football players, four phyla, 10 genera, and four species with densities above 1% were found. Body fat percentage was observed to be negatively correlated with the species of Faecalibacterium prausnitzii and Bacteroides vulgatus and the genus of Faecalibacterium (P<0.05). Considering the nutritional status, the fat intake was found to be positively correlated with Actinobacteria and Blautia coccoides; energy and fiber intake with Prevotella and Prevotella copri (P<0.05). In addition, there was a negative correlation between carbohydrate intake and Faecalibacterium (P<0.05). CONCLUSIONS: Our study is the first to reveal the microbiota profile of professional Turkish football players. It was found that football players` nutritional status and anthropometric measurements of are significantly related to phylum, genus and species ranks in the microbiota. These results support the bidirectional interaction between microbiota and sports. The relationship between microbiota and sports health/performance is thought to be further clarified with future studies.